Study of satisfaction degree of the employees in the Directorate of Social Affairs in the province of Lattakia on The quality of health services provided in the National Hospital. - Mohammad, Osama (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at identifying the level of quality of health services provided in the National Hospital in Latakia city, from the viewpoint of employees in the Directorate of Social Affairs, and determine the level of satisfaction of the beneficiaries of the health services provided in the hospital, according to the study sample. The study population consisted of the employees in the Directorate of Social Affairs who experienced the medical services of the National Hospital in Latakia. The researcher used the descriptive analytical method to measure the satisfaction of the beneficiaries of the quality of health services provided in the National Hospital; a questionnaire was designed and distributed to the beneficiaries of health services in order to measure the quality of services in the mentioned hospital; data have been studied and analyzed with the help of SPSS program, hereafter the results (data analysis) show that the health services provided in the National Hospital in Lattakia fell short of the quality from the viewpoint of employees in the Directorate of Social Affairs according to the dimensions of the quality of health services (tangibility, reliability, responsiveness, empathy, trust and safety).